Economies of private trees: impact on income distribution at Badikhel, (Lalitpur, Nepal) - Kanel, Keshav R.; Sharma, Anuja R. (Banko Janakari, 2017)
Abstract on the PDF Banko Janakari Vol.13(2) 2003: 8-13